The Teacher as the Main Agent in Learning Quality Assurance: Dimension of Personal Aids - Martišauskienė, Elvyda (Acta Paedagogica Vilnensia, 2016)
The quality of learning is linked with authentic meaningful learning based on experience and on subordination of physical, psychical and spiritual powers. Creating educational interaction, a teacher presupposes a transition from educational technology to a learner as a subject and empowers his or her intellectual, emotional and practical activity.Pedagogical interaction is founded on pedagogical power, pedagogical love, pedagogical humour, tact and optimism, which are referred to as teacher’s personal aids and serve as mediators between the familiar reality and a learner.Pedagogical power is centred around the teacher’s internal and spiritual power, which evokes a learner to mobilise own powers for attainment of (self-)education goals. In daily practice pedagogical power unfolds through linking of the taught subject content and personal relations with the supreme values and spiritualisation.Pedagogical love is grounded on the act of self-donation as the supreme expression of authentic relations. However, it is necessary to avoid psychologism, which eliminates the spiritual essence of love that educates rather than rules.Pedagogical humour and tact is a perfect means of tension prevention contributing to strengthening of learners’ self-control mechanisms.Pedagogical optimism reaches origins of existence, which enables to believe in each individual’s capability of being educated, as the key methodological approach, considering the level of learners’ knowledge and abilities, learning pace, methods and orientation.Efficient use of pedagogical means is founded on pedagogical interaction. Therefore, a mature personality of a teacher becomes a measure, which presupposes success and meaning of learning.
Keywords: quality of learning; pedagogical power; pedagogical love; humour; tact; optimism